Aprender haciendo - Martínez Silva, Mayreya Eugenia (Rastros Rostros, 2023)
Pedagogy refers to the particular way of teaching a language along with the theories of how, for what, with what, where, when, and to whom. Differences in the instructional specifications of a second language reflect comparisons in the theories that frame pedagogy.